Banning Childlike Sex Dolls - Monique Hendriks-Lundh (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract This article examines legislative and political developments in Denmark and Norway from 2016 until 2022 on the topic of banning ‘child sex dolls’, i.e. ‘dolls that appear as/look like children’. In Norway, court cases are the focal point for the criminalisation/banning of child sex dolls and are therefore central to this article. A series of cases resulted in the Norwegian Supreme Court (finally) rendering a verdict in September 2019, where it decided that child sex dolls are to be considered forbidden as they imply a ‘sexualisation of children’, which is prohibited by Section 311 of the  Norwegian Criminal Code. In Denmark, the focus lies in the political debate. One Danish political party suggested banning such dolls in 2016, but this was rejected by the Parliament. Since then, the debate has gone back and forth, primarily relying on advice from relevant organisations, i.a. Save the Children Denmark, until a bill banning the dolls was presented in November 2021. The article concludes that the scientific research is too scarce, i.e. that we have insufficient knowledge on the effect on the users of child sex dolls. We do not know whether continuously allowing the purchase and possession of child sex dolls leads to an increased number of sexual assaults against  children – or a decline in that number. Experts argue that as long as we lack any solid evidence that the use of these dolls has a harmful effect it is heedless, and may even be risky, to ban them. The majority political opinion has changed over time, going from ‘we need more knowledge on the matter’ to ‘we need to protect the interests of the children, and the doubt of the harmful effect of the use of the dolls should be in the children’s benefit’. This change, however, has occurred in the absence of any scientific research to support it.